Design of univariate alarm systems via rank order filters. (February 2017) - Tan, Wen; Sun, Yongkui; Azad, Ishtiza Ibne; Chen, Tongwen
Abstract: Filtering is one of the techniques used in alarm system design to improve the performance of an alarm system. Due to the fact that the filtered data is no longer independent, computation of the performance indexes (false alarm rate (FAR), missed alarm rate (MAR) and expected detection delay (EDD)) is hard for filters. In this paper, rank order filters are applied in alarm system design. The output of rank order filters is restricted to one of the input samples, thus the probability density function (PDF) of the filtered data can be computed directly from the PDF of the raw data. This feature makes it possible to compute FAR and MAR for rank order filters directly. Further, a method to compute the expected detection delay is proposed for rank order filters despite the dependence of the filtered data. Simulation results shows that the order of rank order filters provide another degree-of-freedom in alarm system design besides the window size, which can be used to improve the alarm performance. Abstract : Highlights: Rank order filters are applied in alarm system design. A method is proposed to compute the accuracy (FAR and MAR) of an alarm system with rank order filters. A method is proposed to estimate the detection delay for an alarm system with rank order filters. The order of rank order filters provides another degree-of-freedom in alarm system design in addition to the window size.